2017
DOI: 10.4103/jomfp.jomfp_231_15
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin expression and clinicopathologic correlation of oral hyperplastic reactive lesions: An institutional 6-year retrospective study

Abstract: Background and Objective:Reactive proliferations of oral cavity comprise pyogenic granuloma (PG), fibrous hyperplasia (FH), peripheral ossifying fibroma (POF), and peripheral giant-cell granuloma (PGCG). They often pose diagnostic challenges due to their overlapping clinical and histopathological features. This study was conducted to determine the frequency and clinicopathological correlation of reactive hyperplastic lesions in the oral cavity reported in our institute and compared it with other previous studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…Furthermore, numerous studies have shown that OPN is expressed in inflammation by macrophages and is also activated at sites of ectopic pathologic calcification. 7,13,14 It is possible that inflammation associated with MOP induced the development of the POF described in the present study.…”
Section: Case Reportmentioning
confidence: 79%
See 1 more Smart Citation
“…Furthermore, numerous studies have shown that OPN is expressed in inflammation by macrophages and is also activated at sites of ectopic pathologic calcification. 7,13,14 It is possible that inflammation associated with MOP induced the development of the POF described in the present study.…”
Section: Case Reportmentioning
confidence: 79%
“…12 Upon immunohistochemical examination, reactive gingival nodules including POF have been shown to express osteopontin (OPN). 7,13 OPN is a matricellular…”
Section: Discussionmentioning
confidence: 99%
“…Epulis is a very common oral disease with a prevalence of varying from 5.6 to 20.6% [ 5 , 9 11 ]. The overgrowth of the gingival has multiple impacts including aesthetic problems, functional disorders, difficulty in chewing and speech, even serious psychological problems [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…RLs often pose diagnostic challenges due to their overlapping clinical features [14]. Therefore, the differential diagnosis of PGCG includes besides the other reactive lesions [13], fibrous epulis, peripheral odontogenic fibroma, papilloma, hemangioma, lymphangioma, metastatic tumors of gingiva, nevi or other nodular melanomas and other inflammatory hyperplastic lesions [15,16] all of which present with similar clinical and radiographic findings.…”
Section: Discussionmentioning
confidence: 99%